Evaluation of the Implementation of Tax Planning as an Effort to Minimize the Tax Burden in the Context of Tax Management: Evaluasi Penerapan Tax Planning Sebagai Upaya Meminimalkan Beban Pajak dalam Rangka Manajemen Pajak - Ida Agustin; Herman Ernandi (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to analyze the evaluation of the implementation of tax planning as an effort to minimize the tax burden in the context of tax management at Pt Supreme Surabaya Motor Service. The sampling method used is qualitative research and is included in descriptive analysis research. research location at PT Supreme Surabaya Motor Service. The data collection that was carried out were interviews, documentation, and observations. Test the validity of the data carried out in this study by using the Triangulation Test. Activities in data analysis in this study are data collection, data reduction, data display, and conclusion drawing/verification. The results of this study indicate that based on the results of the study it can be seen that the tax planning strategy that has been applied by PT. Supreme Surabaya Motor Service with positive and negative corrections to accounts that are not recognized by tax either as income or as an expense resulted in reduced taxable income and the decrease in income caused income tax payable to also decrease. The results of research on optimizing tax planning conducted by PT. Supreme Surabaya Motor Service in terms of taxation can generate tax savings of Rp. 4,561,625,168 and the profit obtained by the company after deducting income tax is Rp. 62,671,215,713.